DETERMINATION OF PARTNERSHIP PATTERNS IN SCIENCE TECHNO PARK (STP) SOUTH SUMATRA - Hatta, Hendrixon (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2019)
STP of South Sumatra which is a development of the ATP which has existed since 2006 is located in Bakung Village, Ogan Ilir Regency. STP South Sumatra has a major obstacle in the management of existing agriculturally and livestock businesses that have so far used the PIR (Perkebunan Inti Rakyat) partnership. The purpose of this study is determine the right partnership for the agriculture and livestock business of South Sumatra STP and formulate the management strategy of South Sumatra STP. This research was conducted with a qualitative descriptive method using primary and secondary data collection with the help of questionnaires and interviews with farmers and STP Sumsel. From the results of this study, the contract partnership pattern can be applied in South Sumatra STP because it can guarantee the availability of raw materials for South Sumatra STP farms and guarantee the purchase of agricultural products from partner farmers. From the SWOT analysis, a strategy that can be implemented by South Sumatra STP is contract partnership with farmers, involving professionals, making standard operational procedures, and dynamic management of STP Sumsel institutions.